2014
DOI: 10.1590/s0080-6234201400005000006
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to anti-hypertensive treatment within a chronic disease management 
program: A longitudinal, retrospective study

Abstract: Objective This study assessed pharmacological treatment adherence using the Morisky-Green Test and identified related variables. Method A longitudinal and retrospective study examined 283 patients with hypertension (62.5% women, 73.4 [10.9] years old) who were being monitored by a chronic disease management program for 17 months between 2011 and 2012. Nurses performed all the actions of the program, which consisted of advice via telephone and periodic home visits based on the risk stratification of the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
(17 reference statements)
1
17
0
4
Order By: Relevance
“…The median sample size for all surveyed studies was 885 participants (range 109‐7425), with a total of 27 441 participants included in this review. Eleven studies were based in North America, 7 in Asia, 5 in South America, 4 in Europe, 2 in Africa, and 3 were conducted in multiple countries . The most common condition studied was Hypertension (n = 27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median sample size for all surveyed studies was 885 participants (range 109‐7425), with a total of 27 441 participants included in this review. Eleven studies were based in North America, 7 in Asia, 5 in South America, 4 in Europe, 2 in Africa, and 3 were conducted in multiple countries . The most common condition studied was Hypertension (n = 27).…”
Section: Resultsmentioning
confidence: 99%
“…The studies reported the outcomes in 4 ways: overall non‐adherence to medication (n = 10), non‐adherence to individual classes of medications (n = 11), overall adherence to medication (n = 8) and adherence to individual classes of medications (n = 2) . Prevalence of overall non‐adherence to medication ranged from 8.2 to 74.9%; whereas non‐adherence to individual classes of medication ranged from 4.0 to 75.8%; overall adherence to medication ranged from 21.2 to 78%; and adherence to individual classes of medication ranged from 15.0 to 77.4%.…”
Section: Resultsmentioning
confidence: 99%
“…, p. 42). The work of nurses with hypertensive patients is essential in terms of adherence to administered treatment, which requires medium‐term and long‐term lifestyle changes by these individuals (Raymundo & Pierin ).…”
Section: Discussionmentioning
confidence: 99%
“…Taking it into consideration, it is up to the health professionals to support the hypertensive individual in the perspective of the extension of the care, so that it is understood in its individuality, through the approach centered in the patient and in the interactivity. Those actions contribute so that the HTN individual becomes responsible for his/ her own health (13) . It is considered as non-adherence to treatment of HTN when use of the medicine does not match partially or completely with the treatment plan and, when referring to the sufferers of HTN, comes to be regarded as an invisible epidemic, but its prevalence varies with the method used and is higher in developing countries, such as Brazil (8) .…”
Section: Introductionmentioning
confidence: 99%